Ferrocene self assembled monolayer as a redox mediator for triggering ion transfer across nanometer-sized membranes. (20th August 2019) - Cuartero, Maria; Chai, Lijun; Zhang, Biaobiao; De Marco, Roland; Crespo, Gastón A.
Abstract: Modulation of ion-transfer processes across nanometer-sized voltammetry membranes by ferrocene-based self-assembled monolayer on regular glassy carbon electrode is herein demonstrated. The composition of the membrane is advantageously tuned to promote either cation or anion transfer: the presence of an exchangeable cation results in cation transfer, whereas a lipophilic salt induces anion transfer through the fulfilment of the electroneutrality of the system. When an anodic scan oxidizes ferrocene moieties in the monolayer, these are stabilized by the pairing of lipophilic anions present in the membrane. As a result, either, hydrophilic cations present in the membrane are expelled into the solution or anions enter from the solution generating hence reversible and voltammetric waves for these transfers. The use of a redox active monolayer rather than a conducting polymer film or a redox active compound into the membrane overcomes a number of drawbacks previously manifested by these systems. The confinement of the redox process in a thin film at the immediate vicinity of the membrane allows to avoid the need of elevated number of redox moieties to be sued in the membrane, therefore suppressing its acute leaching and being compatible with the incorporation of both cation and anion ionophores for the first time. In this sense, assisted transfer of lithium and chloride are shown as proof-of-concept. Here, the peak potential of the associated voltammetric waves shifts according to the Nernst equation, in analogy to potentiometric sensors. Analytical detection of lithium and chloride ions in real samples is additionally presented. Graphical abstract: Image 1 Highlights: Redox active self-assembled monolayers effectively modulate ion-transfer processes. Nanometer-sized membranes are tuned to get both cation and anion transfer. The system is compatible for the first time with cation and anion ionophores. Detection of lithium in urine and chloride in tap water is demonstrated.